Analisis Bibliometric : Pengaruh Pasca Covid-19 terhadap Penerimaan Pajak - Diva Ayu Rahma Mauluddyah; Wahyu Helmy Damayanti Sukiswo (Journal Of Business, Finance, and Economics (JBFE), 2024)
The purpose of this study is to map research topics and develop further research directions on the post-Covid 19 impact on tax revenues. With this research, the author also gets new keywords that can be used as future research topics. This study is a literature review that uses bibliometric analysis methods and analyzes 50 articles related to post-Covid 19 tax revenue. Bibliometric analysis was performed using the VOSviewer analysis tool. The articles were retrieved from the Google Scholar database accessed through the Publish or Perish service between 2020 and 2024. According to the results of this study, topics related to the impact on tax revenues after Covid 19 are an interesting research topic. There are some specific words that can be further explored in relation to post-Covid 19 tax revenue topics, namely the Covid-19 pandemic, tax revenue and tax policy. Hopefully, this study will provide ideas and thoughts to guide further research.